Mulat Sarira Karya Komposisi Karawitan - Saba, I Ketut (Acintya, 2009)
Mulat Sarira(Bali language) literally means self instropection. This term is often used in dialogue or monologue in lakon for dance drama, wayang, or other performing arts. Mulat Sarira is also used as a title of Karawitan Composition. It started from the idea of the writer’s anxiety towards social phenomena which tends to be unnatural. This work tries to reflect human attitude which do not obey the rule, which is not afraid, ashamed, and sinful when they do unrespectable deed. Instropection becomes a realizing expression through oral tradition approach (it is dominant in Hindu spiritual practices) and that is a purpose of this work. Vocal becomes an important and dominant element in this work for it is placed as a medium for religious advice giving which is hoped to affect the spiritual and physical harmony in social life.Keyword : social phenomena, realizing, treatment(garap), vocal vocabulary.